Resist the punitive state : grassroots struggles across welfare, housing, education and prisons - Hart, Emily Luise; Greener, Joe; Moth, Rich (Pluto Press, 2020)
To examine government policy and state practice on housing, welfare, mental health, disability, prisons or immigration is to come face-to-face with the harsh realities of the 'punitive state'. But state violence and corporate harm always meet with resistance. With contributions from a wide range of activists and scholars, 'Resist the Punitive State' highlights and theorises the front line of resistance movements actively opposing the state-corporate nexus. The chapters engage with different strategies of resistance in a variety of movements and campaigns. In doing so the book considers what we can learn from involvement in grassroots struggles, and contributes to contemporary debates around the role and significance of subversive knowledge and engaged scholarship in activism. Aimed at activists and campaigners plus students, researchers and educators in criminology, social policy, sociology, social work and the social sciences more broadly, 'Resist the Punitive State' not only presents critiques of a range of harmful state-corporate policy agendas but situates these in the context of social movement struggles fighting for political transformation and alternative futures.